1
$\begingroup$

In algebraic geometry one proves that the affine coordinate ring of $\mathbb{P}^n$ is trivial by using that the only polynomials $f$ satisfying $f(\lambda x_0,\ldots,\lambda x_n) = f(x_0,\ldots,x_n) $ are the constant polynomials. Geometrically this is obvious, if we're dealing with polynomials over $\mathbb{R}$ at least, but I'm also not sure how to prove it.

Question. How do we know that the only polynomials $f$ satisfying $f(\lambda x_0,\ldots,\lambda x_n) = f( x_0,\ldots,x_n) $ are the constant polynomials?

Remark. Robert Lewis solved this by assuming the identity was true for all $\lambda.$ However AFAIK, in the context of algebraic geometry we only know that it's true for all non-zero. Perhaps it's possible to adapt his proof somehow?

$\endgroup$
  • 2
    $\begingroup$ Let $k$ be the base field. For a fixed $\left(x_0,\ldots,x_n\right)\in k^{n+1}$, $$P(\lambda):=f\left(\lambda x_0,\ldots,\lambda x_n\right)$$ is a polynomial in variable $\lambda$ with coefficients in $k$. If we know $$P(\lambda)=P(1)$$ for infinitely many $\lambda$ in $k$, then $P(\lambda)$ is constant, whence $$P(\lambda)=P(0)$$ for all $\lambda \in k$, so Robert Lewis's answer is still valid, as long as there are infinitely many $\lambda\in k$ such that $P(\lambda)=P(1)$. In particular, if the field is infinite and if $P(\lambda)=P(1)$ for all nonzero $\lambda$, then $P(\lambda)=P(0)$. $\endgroup$ – Batominovski Sep 19 '18 at 8:15
3
$\begingroup$

I am suspicious about the premise of your question: one cannot prove that the coordinate ring of $\mathbb{P}^{n}_{k}$ is $k$ this way without further assumptions on $k$, since otherwise it is not true that the only polynomials $f \in k[X_{0}, \ldots, X_{n}]$ satisfying $f(\lambda X_{0}, \ldots, \lambda X_{n}) = f(X_{0}, \ldots, X_{n})$ for all $\lambda \in k^{\times}$ are the constant polynomials. Indeed, suppose $k$ is the finite field with $p^{n}$ elements, and take (e.g.) $f = 1+X_{0}^{p^{n}-1}$. In this case, $$f(\lambda X_{0}, \ldots, \lambda X_{n}) = 1+(\lambda X_{0})^{p^{n}-1} = 1+\lambda^{p^{n}-1}X_{0}^{p^{n}-1} = 1 + X_{0}^{p^{n}-1},$$ for all $\lambda \in k^{\times}$, since every such element satisfies $\lambda^{p^{n}-1} = 1$.

If $k$ is not finite, then your claim is true. The way to see it is this: suppose $f$ is nonconstant. The ring $k[X_{0}, \ldots, X_{n}]$ has a natural grading on it, namely that of monomial degree; let $g$ be the homogeneous summand of $f$ of greatest degree $d > 0$. It is not hard to see that if $g$ is homogeneous of degree $d$, then $g(\lambda X_{0}, \ldots, \lambda X_{n}) = \lambda^{d}g(X_{0}, \ldots, X_{n})$. Hence, since multiplying each variable argument by $\lambda$ does not change the degree of any monomial term, we see that $f(\lambda X_{0}, \ldots, \lambda X_{n}) = f(X_{0}, \ldots, X_{n})$ can hold only if $\lambda^{d} = 1$. Since there are only finitely many $d$th roots of unity in $k$, and $k$ is infinite, $f(\lambda X_{0}, \ldots, \lambda X_{n}) = f(X_{0}, \ldots, X_{n})$ can hold for at most finitely many nonzero elements of $k$. (You can see that there is not necessarily any contradiction if $k$ is finite via the example above!)

$\endgroup$
9
$\begingroup$

If

$f(\lambda x_0, \lambda x_1, \ldots, \lambda x_n) = f(x_0, x_1, \ldots, x_n) \tag 1$

for all $\lambda$ in some (base) field, then taking $\lambda = 0$, $(x_0, x_1, \ldots, x_n)$ arbitrary yields

$f(x_0, x_1, \ldots, x_n) = f(0 \cdot x_0, 0 \cdot x_1, \ldots, 0 \cdot x_n) = f(0, 0, \ldots, 0), \tag 2$

which looks pretty constant to me.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.